Efficient preparation of dual-emission ratiometric fluorescence sensor system based on aptamer-composite and detection of bis(2-ethylhexyl) phthalate in pork. (1st August 2021) - Wang, Yueying; Li, Wenting; Hu, Xuetao; Zhang, Xinai; Huang, Xiaowei; Li, Zhihua; Li, Miaoyun; Zou, Xiaobo; Shi, Jiyong
Highlights: MoS2 QDs/CdTe-Apta ratiometric fluorescence sensor system was proposed for DEHP detection in pork. Further validation of the fluorescence quenching mechanism. MoS2 QDs/CdTe-Apta has better detection stability than the single-emission CdTe-Apta. Abstract: A ratiometric fluorescence sensor system is proposed for detecting bis(2-ethylhexyl) phthalate (DEHP) in pork, which is based on aptamer recognition with molybdenum disulfide quantum dots and cadmium telluride quantum dots (MoS2 QDs/CdTe-Apta). Two signals exist in the system, among which the response signal is transmitted by CdTe-Apta. The amide condensation between aptamers and CdTe QDs shortens the distance between CdTe QDs and DEHP, thus quenching the fluorescence of CdTe QDs, possibly through a photoinduced electron transfer mechanism. The MoS2 QDs deliver the self-calibration signal, and the fluorescence of MoS2 QDs remains almost constant when co-existing with DEHP. Linearity (R 2  = 0.9536) was established for the DEHP concentration range 0.005–3.0 mg·L −1, with a limit of detection of 0.21 μg·L −1 . The system was successfully applied in the determination of DEHP in pork. The system has potential for the quantitative determination of DEHP in practical applications.